Evaluation of the professional development stake model for geography teachers in Jambi city - Nurhidayanti, Mega; Isa, Nor Kalsum Mohd; Nursa'ban, Muhammad (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
The research aims to assess the Continuous Professional Development (CPD) of geography teachers, addressing: 1) the CPD profile at each level of the stake evaluation model and 2) recommendations based on the Minister of State Regulation Utilization of State Apparatus and Bureaucratic Reform Number 16 of 2009, regarding the Teacher's Functional Department and Credit Score Article 11, which mandates teachers to engage in self-development activities, scientific publications, and innovative works over the past 10 years (2012-2022). The research employs a quantitative descriptive approach utilizing the Stake Model Evaluation, covering the antecedent (planning), transaction (process), and outcomes (results) levels. Primary data collection involves questionnaires supplemented by observations, interviews, and documentation as needed. Data analysis utilizes a percentage approach at each level. Research respondents, selected through disproportionate Random Sampling, include 19 schools in Jambi City, comprising a total of 32 Geography Teachers. Data presentation follows a quantitative descriptive approach. The research findings indicate that: 1) the CPD profile of geography teachers at the antecedent (planning) level is in the good category (79%), the transaction (process) level is also in the good category (84%), while the outcomes (results) level is in the less category (13%). 2) Recommendations at the antecedent level include engaging in enrichment activities. Transaction-level recommendations suggest improving digital skills and supplementing infrastructure facilities with CPD-related books. Outcome-level recommendations propose that the Education Department implement continuous teacher construction. Schools are encouraged to manage teacher's academic qualifications. Geography teachers are urged to contribute to educational works.